Preventing Cervical Cancer in the United States: Barriers and Resolutions for HPV Vaccination - Beavis, Anna Louise; Levinson, Kimberly L. (Frontiers in Oncology, 2016)
HPV vaccination rates for preadolescent and adolescent girls in the United States are far behind those of other developed nations. These rates differ substantially by region and state, socioeconomic status, and insurance status. In parents and young women, a lack of awareness and a misperception of the risk of this vaccine drive low vaccination rates. In physicians, lack of comfort with discussion of sexuality, and the perception that the vaccine should be delayed to a later age contribute to low vaccination rates. Patient and physician-targeted educational campaigns, systems-based interventions, and school-based vaccine clinics offer a variety of ways to address the barriers to HPV vaccination. A diverse and culturally appropriate approach to promoting vaccine uptake has the potential to significantly improve vaccination rates in order to reach the Healthy People 2020 goal of over 80% vaccination in adolescent girls. This article reviews the disparities in HPV vaccination rates in girls in the United States, the influences of patients’, physicians’ and parents’ attitudes on vaccine uptake, and the proposed interventions that may help the US reach its goal for vaccine coverage.